Toxicity of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in the developing male Wistar(Han) rat I: no decrease in epididymal sperm count after a single acute dose - Bell, David Robert; Clode, Sally; Fan, MingQi; Fernandes, Alwyn; Foster, Paul M D; Jiang, tao; Loizou, George; MacNicoll, Alan; Miller, Brian G; Rose, Martin; Tran, Lang; White, Shaun (Oxford University Press, 2007)
It has been reported that fetal exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) causes defects in the male reproductive system of the rat. We set out to replicate and extend these effects using a robust experimental design. Groups of 75 (control vehicle) or 55 (50, 200 or 1000 ng of TCDD kg-1 bodyweight) female Wistar(Han) rats were exposed to TCDD on Gestational Day (GD) 15, then allowed to litter. The high dose group dams showed no sustained weight loss compared to control, but four animals had total litter loss. Pups in the high dose group showed reduced body weight up till day 21, and pups in the medium dose group showed reduced body weight in the first week post partum. Balano-preputial separation (BPS) was significantly delayed in the high dose group male offspring. There were no significant effects of treatment when the offspring were subjected to a functional observational battery, or mated with females to assess reproductive capability. 25 males per group were killed on post natal day (PND) 70, and ~60 animals per group (~30 for the high dose group) on PND120 to assess seminology and other endpoints. At PND120, the two highest dose groups showed a statistically significant elevation of sperm counts, compared to control; however, this effect was small (~30%), within the normal range of sperm counts for this strain of rat, was not reflected in testicular spermatid counts nor PND70 data, and is therefore postulated to have no biological significance. Although there was an increase in the proportion of abnormal sperm at PND70, seminology parameters were otherwise unremarkable. Testis weights in the high dose group were slightly decreased at PND 70 and 120, and at PND120, brain weights were decreased in the high dose group, liver to body weight ratios were increased for all three dose groups, with an increase in inflammatory cell foci in the epididymis in the high dose group. These data show that TCDD is a potent developmental toxin after exposure of the developing fetus, but that acute developmental exposure to TCDD on GD15 caused no decrease in sperm counts.